2004
DOI: 10.1093/humrep/deh146
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone down-regulates insulin-like growth factor-I expression in cultured human uterine leiomyoma cells

Abstract: The present study provided evidence for the first time that progesterone down-regulates IGF-I mRNA and protein expression in cultured leiomyoma cells without affecting IGF-I receptor mRNA expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 31 publications
2
26
1
1
Order By: Relevance
“…The Maruo group in Japan found that progesterone downregulates expression of insulinlike growth factor-I (IGF-1) in human leiomyoma cells (57). They also demonstrated that progesterone upregulates expression of proliferating cell nuclear antigen (PCNA) and epidermal growth factor (EGF), both are known regulators of leiomyoma cellular proliferation (58,59).…”
Section: Progesteronementioning
confidence: 99%
“…The Maruo group in Japan found that progesterone downregulates expression of insulinlike growth factor-I (IGF-1) in human leiomyoma cells (57). They also demonstrated that progesterone upregulates expression of proliferating cell nuclear antigen (PCNA) and epidermal growth factor (EGF), both are known regulators of leiomyoma cellular proliferation (58,59).…”
Section: Progesteronementioning
confidence: 99%
“…There was also a slightly lower neonatal ponderal index in the 400-mg progesterone group (Table 2). Although it is known that progesterone down-regulates insulin-like growth factor 1 (IGF-1) mRNA and protein expression in cultured uterine leiomyoma cells, 23 it seems unlikely that this subtle effect of 400 mg of progesterone on the fetal growth rate of twins could be attributed to a potential IGF-1 down-regulation, because the proportion of neonates with birthweights <2500 g and <1500 g in the 400-mg progesterone group was similar to the other two groups studied.…”
Section: Vaginal Progesterone In Twin Pregnanciesmentioning
confidence: 99%
“…Portier et al showed medium with 2% horse serum or Ultroser ® -G to cause muscular differentiation in myoblasts, whereas 10% fetal calf serum does not support differentiation [29]. Using media without any serum could be advantageous for the density of PR [30]. Myoma tissues were cultured in different concentrations in fetal calf serum (FCS), horse serum (HS), Ultroser ® -G (CytoGen), and without any serum or serum replacement.…”
Section: Optimal Serum For Culturing Myoma Tissuementioning
confidence: 99%